2020
DOI: 10.1038/s41598-020-60889-4
|View full text |Cite
|
Sign up to set email alerts
|

Latitudinal consistency of biomass size spectra - benthic resilience despite environmental, taxonomic and functional trait variability

Abstract: Global warming is expected to cause reductions in organism body size, a fundamental biological unit important in determining biological processes. Possible effects of increasing temperature on biomass size spectra in coastal benthic communities were investigated. We hypothesized higher proportions of smaller size classes in warmer conditions. Soft bottom infauna samples were collected in six norwegian and Svalbard fjords, spanning wide latitudinal (60-81°N) and bottom water temperature gradients (from −2 to 8 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
2
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 72 publications
0
22
2
1
Order By: Relevance
“…That is why the temperature increase due to global warming is likely to cause a change in average individual size, or selection toward smaller species in communities (Atkinson & Sibly, 1997). Such a pattern has already been demonstrated in pelagic Copepoda (Beaugrand, Ibanez, & Reid, 2000), but it is not yet universal in benthic communities (Mazurkiewicz, Górska, Renaud, & Włodarska‐Kowalczuk, 2020). The blurred size pattern among soft‐bottom benthos is due to the dominance of polychaete worms and bivalves—two groups in which linear growth is difficult to assess.…”
Section: Introductionmentioning
confidence: 73%
“…That is why the temperature increase due to global warming is likely to cause a change in average individual size, or selection toward smaller species in communities (Atkinson & Sibly, 1997). Such a pattern has already been demonstrated in pelagic Copepoda (Beaugrand, Ibanez, & Reid, 2000), but it is not yet universal in benthic communities (Mazurkiewicz, Górska, Renaud, & Włodarska‐Kowalczuk, 2020). The blurred size pattern among soft‐bottom benthos is due to the dominance of polychaete worms and bivalves—two groups in which linear growth is difficult to assess.…”
Section: Introductionmentioning
confidence: 73%
“…In contrast, Dossena et al (2012) found that slopes declined with temperature, but the effect varied over seasons. Mazurkiewicz et al (2020) found no relationship between marine benthic size spectra and temperatures in arctic systems. These contrasting outcomes, derived from different experimental approaches, generate uncertainty in how size spectra slopes should scale with temperature across large spatial gradients.…”
Section: Discussionmentioning
confidence: 78%
“…Size spectra are one of the few well documented organizing principles in ecology. A large body of literature has demonstrated the consistency of size-spectra relationships in diverse ecosystems (Jennings & Blanchard 2004;Trebilco et al 2013;Blanchard et al 2017;Mazurkiewicz et al 2019Mazurkiewicz et al , 2020. A strongly negative relationship between the abundance or biomass of individuals for a given body size range has been consistently documented in aquatic communities, to the point that size-spectra parameters have been recommended as a potential "universal" indicator of ecological health (Petchey & Belgrano 2010).…”
Section: Introductionmentioning
confidence: 99%
“…A segunda classificação refere-se ao tamanho da malha do aparato amostral em que o organismo ficou retido, logo chamamos de microbentos os organismos menores que 0,63 mm, meio fauna os organismos entre 0,63 e 0,5 mm e macrofauna os organismos maiores que 0,5-1,0 mm (WILSON; FLEEGER, 2012;KENNISH, 2016). Porém esta última classificação vem sendo cautelosamente revista, dadas às variações nos tamanhos corporais de acordo com a qualidade do alimento e latitude (MAZURKIEWICZ et al, 2020;WARWICK;CLARKE, 1984). Outra questão refere-se à mobilidade dos organismos, eles podem ser sésseis ou fixos e errantes ou móveis.…”
Section: 31caracterização Da Fauna Macrobentônicaunclassified